History as prelude: Muslims and Jews in the medieval Mediterranean - Montville, Joseph V. (Lexington Books, 2011)
This collection of essays by seven scholars is a straightforward narrative of real world-intellectual, commercial, spiritual, philosophical, scientific, esthetic-creative engagement among Jews, Muslims, and some Christians in daily life in Spain and around the Mediterranean. History as Prelude is a major contribution to the Israeli-Arab peace process because it undermines-in fact, blows away-the efforts of propagandists who serve governments or political movements to negate the reality of the Arab-Jewish relationship in the medieval Mediterranean. The contributors, in unassuming, well-research